Populist Policymaking: Analyzing Pakistani Perspective - Syed, Qamar Abbas (Journal of Peace, Development and Communication, 2022)
The rise of populist governments around the world provides a unique chance to analyze how populist leaders and parties govern. The substantive and discursive elements of populist policies and decision-making processes are conceptually addressed. This study explains an ideal type of populist policymaking mechanism along with the scope of content, methods, and discourses. In order to analyze the conformity of an actual policymaking mechanism of populist government, we use a qualitative congruence study. The paper claims that an overwhelming response to majoritarian attitudes is distinctive aspect of populist policies. Whereas, populists tend to devalue the role of legal policy institutions or technocratic competence, marginalize veto players and adopt volatile policy changes. Populist leaders frequently employ crisis frames in policymaking and reinforcing polarization in policy stances. Finally, the article concludes that between 2018 and 2022, Pakistan's policymaking tendencies were mainly consistent with ideal type of populist policymaking.